Tata kelola sumber daya air berkelanjutan-berkeadilan : Bagaimana Indonesia memperkuat poros maritim? - Ghina Annaifah, Salsa (EcoProfit: Sustainable and Environment Business, 2024)
Water resources are an important aspect of human survival. However, population growth, urbanization, climate change, agricultural expansion, and industrialization have led to a rapid decline in the quality and availability of water resources. It is estimated that by 2050, the global population will reach 9.7 billion, which will increase the need for water resources. Currently, approximately 2.3 billion people live in water-critical areas, and two-thirds of the global population experiences critical water shortages for at least one month of the year. The United Nations has established Sustainable Development Goals, with a focus on clean water and sanitation. Indonesia, with more than 17,000 islands, has rich water resources but is vulnerable due to urbanization, pollution, and climate change. To overcome these challenges, sustainable water governance is necessary. Indonesia is already experiencing water shortages, and it is estimated that 67% of economic activity will be in areas experiencing water scarcity by 2045. In addition, Indonesia is among the ten largest groundwater-consuming countries, drawing groundwater mainly for domestic use. To overcome this challenge, the government has implemented water governance reforms through regulatory policies and infrastructure improvements. In this context, this research aims to provide an overview of the progress of sustainable water governance in Indonesia and strategies for facing challenges as a maritime axis in sustainable water governance. This study uses a systematic literature review methodology to analyze 69 articles on current water governance practices, sustainable water governance challenges, and strategies for overcoming these challenges. By adopting sustainable water governance, Indonesia can ensure fair and equitable access to water, reduce water-related conflicts, increase access to clean water and sanitation, and strengthen the country's overall environmental and economic resilience.